The Atacama Cosmology Telescope: measurement and analysis of 1D beams for DR4. Issue 5 (1st May 2022) - Lungu, Marius; Storer, Emilie R.; Hasselfield, Matthew; Duivenvoorden, Adriaan J.; Calabrese, Erminia; Chesmore, Grace E.; Choi, Steve K.; Dunkley, Jo; Dünner, Rolando; Gallardo, Patricio A.; Golec, Joseph E.; Guan, Yilun; et al.
Abstract: We describe the measurement and treatment of the telescope beams for the Atacama Cosmology Telescope's fourth data release, DR4. Observations of Uranus are used to measure the central portion (<12 ' ) of the beams to roughly -40 dB of the peak. Such planet maps in intensity are used to construct azimuthally averaged beam profiles, which are fit with a physically motivated model before being transformed into Fourier space. We investigate and quantify a number of percent-level corrections to the beams, all of which are important for precision cosmology. Uranus maps in polarization are used to measure the temperature-to-polarization leakage in the main part of the beams, which is ≲ 1% (2.5%) at 150 GHz (98 GHz). The beams also have polarized sidelobes, which are measured with observations of Saturn and deprojected from the ACT time-ordered data. Notable changes relative to past ACT beam analyses include an improved subtraction of the atmospheric effects from Uranus calibration maps, incorporation of a scattering term in the beam profile model, and refinements to the beam model uncertainties and the main temperature-to-polarization leakage terms in the ACT power spectrum analysis.